A comparative study of ammonia transport across ruminal epithelia from Bos indicus crossbreds versus Bos taurus. (2nd October 2018) - Rabbani, Imtiaz; Braun, Hannah‐Sophie; Akhtar, Tasneem; Liebe, Franziska; Rosendahl, Julia; Grunau, Martin; Tietjen, Uwe; Masood, Saima; Kaessmeyer, Sabine; Günzel, Dorothee; Rehman, Habib; Stumpff, Friederike
Abstract: Absorption of ammonia from the rumen of cattle decreases nitrogen availability for fermentational protein synthesis, leading to increased competition of cattle with humans for protein and enhancing the release of toxic nitrogenous compounds into the environment. Given that differences in feeding and breeding might induce differences in ruminal ammonia transport, we compared electrophysiological, histological, and molecular biological characteristics of ruminal epithelia of Bos indicus crossbreds (Sahiwal‐Mix, SWM) with those of Bos taurus (Holstein‐Friesian, HF). As in HF, the stratified cornified epithelium of SWM expressed claudin 1 and 4. Measurements of ammonia flux (HF) and serosal pH (both breeds) suggested that at a mucosal pH of 6.4, net transport primarily occurred as NH4 + . As shown previously for HF, NH4 + induced a concentration‐dependent rise in short circuit current (Isc ) in SWM that could be further stimulated by the TRP channel agonist menthol. Relative mRNA expression levels for TRPV3, TRPV4, TRPM6, and TRPM7 were significantly lower in SWM than in HF, with TRPA1 expression near the limit of detection. We conclude that uptake of ammonia from the rumen of both breeds occurs electrogenically as NH4 + with functional and molecular biological evidence pointing towards involvement of TRPV3 and TRPV4.